A Survey of Teachers’ Perspectives on the Reception Ability of Younger Students After Emergency Remote Teaching During COVID-19 - Maja Kerneža (Journal of Elementary Education, 2023)
Emergency remote teaching presented many new and unknown situations. Many studies have examined the impact of distance education on children’s learning outcomes, including in the area of first language, particularly in reading and writing skills, and reading literacy. This research examines the area of literature teaching, more specifically the effects of the change in teaching on younger students’ reception ability. One hundred and ninety-six teachers participated in the quantitative, explorative study. Responses indicate that there are moderate and major differences in the receptive skills of elementary students in the first through third grades, compared to students taught prior to the pandemic.